The Jossey-Bass reader on educational leadership - Jossey-Bass Inc. (San Francisco, CA : Jossey-Bass, 2007)
A collection of book excerpts, articles, and reports that addresses six themes in educational leadership, including principles of leadership, moral leadership, culture and change, standards and the system, diversity and leadership, and the future of leadership.
"Give me a lever long enough--and single-handed I can move the world" / Peter M. Senge -- The nature of leadership / John W. Gardner -- Level 5 leadership / Jim Collins -- The unheroic side of leadership : notes from the swamp / Jerome T. Murphy -- The five practices of exemplary leadership / James M. Kouzes and Barry Z. Posner -- Leadership as stewardship : "who's serving who?" / Thomas J. Sergiovanni -- An educational credo for a time of crisis and urgency / David E. Purpel -- Becoming a trustworthy leader / Megan Tschannen-Moran -- The manager as politician / Lee G. Bolman and Terrence E. Deal -- The authentic leader / Robert Evans -- Culture in question / Roland S. Barth -- Understanding change / Michael Fullan -- Transformation school leadership in a transactional policy world / Kenneth A. Leithwood -- Eight roles of symbolic leaders / Terrence E. Deal and Kent D. Peterson -- Risk / Roland S. Barth -- Understanding the normative system / Phillip C. Schlechty -- Power standards : how leaders add value to state and national standards / Douglas B. Reeves -- Standards for school leaders / Interstate School Leaders Licensure Consortium -- Making differences matter : a new paradigm for managing diversity / David A. Thomas and Robin J. Ely -- Teaching all students : celebrating diverse minds / Mel Levine -- Gender and race as factors in educational leadership and administration / Cherry A. McGee Banks -- Gender and supervision / Charol Shakeshaft, Irene Nowell, and Andy Perry -- The work of principals and their preparation : addressing critical needs for the twenty-first century / Carolyn Kelley and Kent D. Peterson -- Teacher leadership : ideology and practice / Ann Lieberman, Ellen R. Saxl, and Matthew B. Miles -- Lasting leadership : a study of high leadership capacity schools / Linda Lambert -- Resourcefulness: restraint and renewal / Andy Hargreaves and Dean Fink.
Includes bibliographical references.
Professional.
Professional
Keywords: Educational leadership -- United States; School management and organization -- United States; Leadership; Schools -- Administration -- United States